-17(-4c+16)=

Simple and best practice solution for -17(-4c+16)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -17(-4c+16)= equation:


Simplifying
-17(-4c + 16) = 0

Reorder the terms:
-17(16 + -4c) = 0
(16 * -17 + -4c * -17) = 0
(-272 + 68c) = 0

Solving
-272 + 68c = 0

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '272' to each side of the equation.
-272 + 272 + 68c = 0 + 272

Combine like terms: -272 + 272 = 0
0 + 68c = 0 + 272
68c = 0 + 272

Combine like terms: 0 + 272 = 272
68c = 272

Divide each side by '68'.
c = 4

Simplifying
c = 4

See similar equations:

| 4x-41=9x+24 | | 3x-2x=-4x+2 | | 13=5m-7-5 | | 12x-7x+1=66 | | 5t+25-11= | | -3(-7y+9)-5y=6(y-7)-1 | | 3x+2(x-10)-5=0 | | 3x+2x+51=180 | | 25-2.45s=47.05 | | X+5-8x=-16 | | 12y^2-y-20= | | -6.3(2y+5)-2.5(4y-6)= | | 5x+9=2x+45 | | 4y-2y+5y-46=126 | | -17(-4+16)= | | v=nr*2n | | 3(y+10)+2y-5=0 | | 9x-38=20x+5 | | 22.33-x=32 | | 31/3x41/6 | | -2(6w-6)+6w=8+2(3w-7) | | 18(-1x+-2)-4(-9+3x)=-14 | | 4t^2+t-60=0 | | 5y+(3y-25)=47 | | 1.3x+4.4=.07x-0.52 | | M=s-c | | -2.5(y-10)-0.166= | | -x+9-4x=-31 | | (5X^-2Y^5/4X^6Y^-3)^-2 | | -(x+4)=3 | | X+5-8x=16 | | 0.13(x+40)+0.4(x+25)=-19.25 |

Equations solver categories